Fibronectin signals through integrin α5β1 to regulate cardiovascular development in a cell type-specific manner - Chen, Dongying (Dev Biol, 2015)
Fibronectin (Fn1) is an evolutionarily conserved extracellular matrix glycoprotein essential for embryonic development. Global deletion of Fn1 leads to mid-gestation lethality from cardiovascular defects. However, severe morphogenetic defects that occur early in embryogenesis in these embryos precluded assigning a direct role for Fn1 in cardiovascular development. We noticed that Fn1 is expressed in strikingly non-uniform patterns during mouse embryogenesis, and that its expression is particularly enriched in the pharyngeal region corresponding with the pharyngeal arches 3, 4, and 6. This region bears a special importance for the developing cardiovascular system, and we hypothesized that the localized enrichment of Fn1 in the pharyngeal region may be essential for cardiovascular morphogenesis. To test this hypothesis, we ablated Fn1 using the Isl1(Cre) knock-in strain of mice. Deletion of Fn1 using the Isl1(Cre) strain resulted in defective formation of the 4th pharyngeal arch arteries (PAAs), aberrant development of the cardiac outflow tract (OFT), and ventricular septum defects. To determine the cell types responding to Fn1 signaling during cardiovascular development, we deleted a major Fn1 receptor, integrin α5 using the Isl1(Cre) strain, and observed the same spectrum of abnormalities seen in the Fn1 conditional mutants. Additional conditional mutagenesis studies designed to ablate integrin α5 in distinct cell types within the Isl1(+) tissues and their derivatives, suggested that the expression of integrin α5 in the pharyngeal arch mesoderm, endothelium, surface ectoderm and the neural crest were not required for PAA formation. Our studies suggest that an (as yet unknown) integrin α5-dependent signal extrinsic to the pharyngeal endothelium mediates the formation of the 4th PAAs.